2010
DOI: 10.1152/ajpgi.00394.2009
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-mediated phagocytosis of apoptotic cholangiocytes contributes to reversal of experimental biliary fibrosis

Abstract: Studies have suggested the reversibility of liver fibrosis, but the mechanisms of fibrosis reversal are poorly understood. We investigated the possible functional link between apoptosis, macrophages, and matrix turnover in rat liver during reversal of fibrosis secondary to bile duct ligation (BDL). Biliary fibrosis was induced by BDL for 4 wk. After Roux-en-Y (RY)-bilio-jejunal-anastomosis, resolution of fibrosis was monitored for up to 12 wk by hepatic collagen content, matrix metalloproteinase (MMP) expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
103
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 124 publications
(109 citation statements)
references
References 46 publications
5
103
0
Order By: Relevance
“…This model is irreversible in mice; however, it is possible to reconnect the bile duct in rat models. 31 Due to wound healing after surgery, this model is usually performed in studies focused on chronic liver injury. Probably, the most important modification of the BDL model is partial BDL (pBDL).…”
Section: Models To Target Cholangiocytesmentioning
confidence: 99%
“…This model is irreversible in mice; however, it is possible to reconnect the bile duct in rat models. 31 Due to wound healing after surgery, this model is usually performed in studies focused on chronic liver injury. Probably, the most important modification of the BDL model is partial BDL (pBDL).…”
Section: Models To Target Cholangiocytesmentioning
confidence: 99%
“…We found a strong upregulation of MMP-2, -3 and -13 in WT mice compared with CB1 -/-animals. This seemingly contradictory observation with regards to the balance between fibrogenesis and fibrolysis can be explained by the very complex and different regulation of MMP expression and enzymatic activation during the peak of fibrosis formation and ECM degradation (34,37). Certain MMPs, such as profibrogenic MMP-2, facilitate and promote degradation of basement membrane with subsequent activation, migration and proliferation of HSC/myofibroblasts, resulting in progression of liver injury and fibrosis (38), whereas others, such as MMP-3, -9 and -13 participate in the degradation of extracellular matrix and fibrosis resolution (35,39).…”
Section: Cb1mentioning
confidence: 99%
“…The reduction of fibrosis within cirrhotic liver tissue would lead to a reduction of portal hypertension and consequent clinical complications, thus improving overall liver function, which would extend the complication-free patient survival time and reduce the need for liver transplants [26] . Studies have suggested the reversibility of liver fibrosis, but the mechanisms for such a reversal are poorly understood [79] . In BDL rats, Popov and colleagues introduced macrophages to damaged biliary epithelium via Roux-en-Y bilio-jejunal anastomosis.…”
Section: Reversal Of Biliary Fibrosismentioning
confidence: 99%
“…In BDL rats, Popov and colleagues introduced macrophages to damaged biliary epithelium via Roux-en-Y bilio-jejunal anastomosis. After engulfing apoptotic cholangiocytes, macrophages upregulate matrix metalloproteinases and become fibrolytic effector cells [79] . This suggests a link between apoptotic epithelial cells, macrophages, and the reversal of fibrosis.…”
Section: Reversal Of Biliary Fibrosismentioning
confidence: 99%